Sulfur Isotope Evidence for a Geochemical Zonation of the Samoan Mantle Plume. (25th June 2021) - Dottin, James W.; Labidi, Jabrane; Jackson, Matthew G.; Farquhar, James
Abstract: Basalts from the Samoan volcanoes sample contributions from all of the classical mantle endmembers, including extreme EM II and high 3 He/ 4 He components, as well as dilute contributions from the HIMU, EM I, and DM components. Here, we present multiple sulfur isotope data on sulfide extracted from subaerial and submarine whole rocks ( N = 16) associated with several Samoan volcanoes—Vailulu'u, Malumalu, Malutut, Upolu, Savai'i, and Tutuila—that sample the full range of geochemical heterogeneity at Samoa and upon exhaustive compilation of S‐isotope data for Samoan lavas, allow for an assessment of the S‐isotope compositions associated with the different mantle components sampled by the Samoan hotspot. We observe variable S concentrations (10–1, 000 ppm) and δ 34 S values (−0.29‰ ± 0.30 to +4.84‰ ± 0.30, 2σ). The observed variable S concentrations are likely due to sulfide segregation and degassing processes. The range in δ 34 S reflects mixing between the mantle origin and recycled components, and isotope fractionations associated with degassing. The majority of samples reveal Δ 33 S within uncertainty of Δ 33 S = 0‰ ± 0.008. Important exceptions to this observation include: (a) a negative Δ 33 S (−0.018‰ ± 0.008, 2σ) from a rejuvenated basalt on Upolu island (associated with a diluted EM I component) and (b) previously documented small (but resolvable) Δ 33 S values (up to +0.027 ± 0.016) associated with the Vai Trend (associated with a diluted HIMU component). The variability we observed in Δ 33 S is interpreted to reflect contributions of sulfur of different origins and likely multiple crustal protoliths. Δ 36 S versus Δ 33 S relationships suggest all recycled S is of post‐Archean origin. Plain Language Summary: Samoa is a group of volcanoes as islands and seamounts that reside in the south Pacific Ocean. This group of volcanoes are unique in that they erupt material from the deep mantle that was once at the surface, suggesting large scale crustal recycling was at play. Furthermore, distinct groupings of volcanoes and seamounts appear to erupt distinct recycled components. However, the nature and relative age of these components are not well understood. We use sulfur isotopes to gain insights into the materials erupted at Samoa. We provide evidence that the mantle plume beneath Samoa is geochemically zoned, as S‐isotopes are distinct at different groups of islands. We also argue that the identified recycled materials are best linked to Proterozoic sulfur and in some cases may represent recycled S reservoirs that are distributed among multiple Pacific Ocean island basalts. Key Points: Basalts from Samoan volcanoes preserve heterogeneous sulfur isotope signatures We observe unique S‐isotope compositions associated with distinct groups of Samoan volcanoes Sulfur isotope variability is associated with multiple distinct recycled components